Ihtikar Menurut Hukum Islam dan Hukum Positif - BONITA IZWANY (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine the concept of Ihtikar according to Islamic lawand positive law. The Islamic economic system prioritizes equality, opportunityand equitable distribution of income. To achieve this equation, Islam prohibitsthe practice of hoarding merchandise in economic activities, because it is anoppression. This study uses the Library Research method (library research).The results of this study, obtained two conclusions. First, the scholars of fiqhboth Malikiyah, Shafi'yah, and Hanabilah prohibit except Hanafiah whichimposes hoarding of merchandise, especially those related to foodstuffs andstaples for the general public, which can cause harm to the community'seconomy, as well as in the positive law the prohibition of hoarding on whenthere is a scarcity of basic and essential commodities, the concept of the lawallows stockpiling in the next three months not until scarcity occurs, it isallowed to hoard to help public and private availability and production,secondly, the similarities between the concept of Ihtikar according to Islamiclaw and positive law are the same prohibits ihtikar actions when there isscarcity of goods, the same prohibition on hoarding foodstuffs and staples ofthe general public in general. The difference is in the provisions on the types ofgoods that cannot be hoarded and the period allowed to hoard